Restenosis Rate and Reinterventions after Aortic Arch Repair in Infants - Iaroslav P. Truba; Oleksandr S. Golovenko; Ivan V. Dziuryi (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. This study aims to determine the reintervention rate in infantsundergoing aortic arch repair and to analyze risk factors and evaluate the results of reinterventions.Materials and methods. This retrospective study examines 445 infants with aortic arch hypoplasia who under-went aortic arch reconstruction between 2011 and 2019. The study included only patients with two-ventricle physiology and subsequent two-ventricle repair. Techniques for primary repair included extended end-to-end anastomosis (n = 348), end-to-side anastomosis (n = 611), autologous pericardial patch repair (n = 16).Results. The overall mortality in the entire study group was 3.3 %. Follow-up period ranged from 1 month to 9.4 years (mean 2.8 ± 2.5 years). Restenosis at the site of aortic arch repair was identiϐied in 47 (10.5 %) patients. Of these, 12 patients underwent surgical reconstruction of the aortic arch, 27 patients underwent balloon angioplasty, and in 8 patients both methods were used. Freedom from reintervention was 89.4 % at 1-year follow-up and 87.5 % at 4-year follow-up. The most determining factorsfor restenosis were related to hypoplastic proximal aortic arch and body weight less than 2.5 kg.Conclusions. Surgical treatment of aortic arch hypoplasia in newborns and infants is effective and shows good immediate and long-term results. Anatomical correction of reobstruction at the level of the aortic arch is safe with both endovacular and surgical methods with low mortality and incidence of repeated interventions. Identified risk factors for mortality and recurrent aortic arch interventions help to improve the treatment of aortic arch hypoplasia in patients under 1 year of age.